Isolation and characteristics of new phage JK004 and application to control Cronobacter sakazakii on material surfaces and powdered infant formula. (January 2022) - Wang, Lihan; Pang, Xinyi; Zhao, Jiayuan; Jin, Haonan; Yang, Xinyan; Fu, Shiqian; Cheng, Shasha; Li, Hongxuan; Miao, Chao; Man, Chaoxin; Jiang, Yujun
Abstract: Cronobacter sakazakii ( C. sakazakii ) is a food-borne pathogen that can be spread by powdered infant formula (PIF) to cause illness in infants. Bacteriophages (phages) are an effective potential strategy to control food-borne pathogens. Phage JK004 which isolated from the native environment of C. sakazakii was a novel virulent phage with short latent period and large burst size. JK004 had tolerance to heat, pH and osmotic-stress. The phage JK004 did not contain known virulence, transduction or antibiotic resistance genes, indicating that JK004 is safe in the practical application. In addition, because of the biofilms formation, C. sakazakii could adhere to material surfaces and was difficult to remove, resulting in persistent contamination of the PIF. JK004 could effectively remove the biofilms that have formed on sterile 96-well plates with 87% inhibition rate. While the inhibition rate of bacteria adhered on the material surfaces such as polyethylene, rubber and stainless steel was 99.95%, 99.83%, 99.84%, respectively, with significant difference between the JK004 treated group and the control group ( p  < 0.05). The antibacterial activity of JK004 against C. sakazakii in PIF was also excellent. This study provides a basis for the potential application of JK004 for controlling of C. sakazakii in food production. Highlights: JK004 was a novel virulent phage with specific lytic activity to C. sakazakii. JK004 had no virulence genes which confirmed its safety in practical applications. JK004 could remove the biofilms that had formed. JK004 had good antibacterial activity to C. sakazakii on material surfaces and PIF.